Application of high-resolution thermal infrared remote sensing for the observation of the urban heat island effect in the area of Limassol, Cyprus - Κaizer, Christiana (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The urban heat island effect is one of the major problems out of other environmental and socioeconomic problems a city can have, that cause urban growth. Due to this phenomenon the rural landscape has been replaced by manmade urban areas with surface that increases the heat carrying capacity and the urban warmth, and therefore, the urban air temperature is higher than that of the surrounding rural environment. In order to evidence the effect of this phenomenon in Cyprus and more specifically in Limassol area, an observation of the temperature fluctuations in the urban and rural areas is done through a methodology which has been followed. Thermal satellite images were taken through Earth Explorer online program of USGS Glovis and elaborated in the ERDAS IMAGINE CLASSIC INTERFACE software, in order to determine these temperature´s fluctuations. Furthermore, a visualization of the various data and results was taken from the study area and through the Excel program, graphs were exported. Through these graphs, the influence of urban heat island effect, in the area of Limassol, through the years was possible to be observed and also, correlations of the phenomenon with other important factors such as location, altitude, distance from the sea, vegetation, population etc. as well as the differences in temperature between urban and rural areas of Limassol were observed.
Keywords: Phenomenon; Environmental; High resolution